Using immersive virtual reality in testing empathy type for adolescents - Kim, Eunha; Laine, Teemu H.; Suk, Hae Jung; Jo, Young Won (Current Psychology, 2024)
Empathy is an important aspect of human interaction that helps individuals form meaningful relationships and connect with others. Although levels of empathy have been measured using paper–pencil tests, there are no tools to identify the different types of empathy. The current study aimed to develop and validate the Virtual Reality Empathy Test (VRET), which was designed to identify adolescent empathy types. The types of empathy were developed based on three pairs of dimensions (cognitive versus affective empathy, positive versus negative empathy, and majority versus minority empathy). VRET consists of three virtual scenarios that include positive and negative situations (e.g., winning a gold medal or losing in the first round of a badminton tournament). As each scenario progressed, the participants were asked to answer 13 questions during the first and second scenarios, and eight questions during the third scenario. The VRET was administered to 90 South Korean high school students. Hypothesized differences between existing empathy scales and VRET results were found, indicating a high convergent and discriminant validity. VRET, as a unique test of empathy type, can be a valuable tool to assist adolescents in developing a balanced sense of empathy.
Keywords: Adolescents; Assessment; Empathy type; Validity; Virtual reality